2018
DOI: 10.4172/pharmaceutical-sciences.1000372
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Role of a Marvel Golden Molecule, Curcumin: a Review

Abstract: Moselhy, et al.: Multifaceted Role of CurcuminCurcumin is chemically known as diferuloylmethane, which is an important nutraceutical obtained from the yellow spice Curcuma longa. It has been used traditionally as a folklore medicine in countries like India, China and Thailand for nearly 2000 years without any prior knowledge of the mechanism of action. Cellbased studies and clinical trials that have been reported so far have provided evidence that curcumin could be effectively used as antimicrobial, anticancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
4
0
1
Order By: Relevance
“…kunyit dilaporkan menghambat pertumbuhan mikroba uji (Escherichia coli, Staphylococcus aureus dan Candida albicans) (Syarif, 2017). Daun kunyit diketahui juga memiliki efek penghambat pertumbuhan Aspergillus flavus dan Fusarium moniliforme (Moselhy, 2018). Konsentrasi ekstrak daun kunyit 15% diketahui memiliki efek penghambatan terhadap bakteri Streptococcus dengan rata-rata diameter hambat sebesar 9,5 mm.…”
Section: Ekstrakunclassified
“…kunyit dilaporkan menghambat pertumbuhan mikroba uji (Escherichia coli, Staphylococcus aureus dan Candida albicans) (Syarif, 2017). Daun kunyit diketahui juga memiliki efek penghambat pertumbuhan Aspergillus flavus dan Fusarium moniliforme (Moselhy, 2018). Konsentrasi ekstrak daun kunyit 15% diketahui memiliki efek penghambatan terhadap bakteri Streptococcus dengan rata-rata diameter hambat sebesar 9,5 mm.…”
Section: Ekstrakunclassified
“…Within this latter organ the increased curcumin bioavailability might counteract cognitive decline. Figure adapted with permission from [ 119 ]. Copyright © 2018, Said Moselhi.…”
Section: Figurementioning
confidence: 99%
“…The protective effect of natural compounds may be attributed to the presence of numerous phytochemicals such as resveratrol, quercetin, rutin, catechin, myricetin, kaempferol, and Epigallocatechin gallate (EGCG). EGCG has been reported to modulate multiple key elements in signal transduction pathways affecting cellular proliferation, differentiation, apoptosis, inflammation, angiogenesis and metastasis in CRC (Araujo et al, 2011;Kuerban et al, 2017;Soengas Fernández et al, 2011;Moselhy et al, 2018). Initial studies have revealed that these compounds are able to affect cell proliferation, cell cycle regulation, and usually participate in multiple signaling pathways which are often disrupted in tumor initiation, proliferation and propagation (Kotecha et al, 2016).…”
Section: Introductionmentioning
confidence: 99%